2020
DOI: 10.1111/ppl.13118
|View full text |Cite
|
Sign up to set email alerts
|

What drives interspecies graft union success? Exploring the role of phylogenetic relatedness and stem anatomy

Abstract: The underlying mechanisms that determine whether two species can form a successful graft union (graft compatibility) remain obscure. Two prominent hypotheses are (1) the more closely related species are, the higher the graft success and (2) the vascular anatomy at the graft junction influences graft success. In this paper these two hypotheses are examined in a systematic way using graft combinations selected from a range of (a) phylogenetically close and more distant legume species, (b) species displaying diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 73 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…Moreover, new and potentially beneficial graft combinations are not explored due to compatibility barriers. Some incompatibility causes are: (a) genetic distance [7,15,16], (b) physiological and/or anatomical difficulties [14,17], (c) toxic compounds transference [18,19], (d) inadequate cell-to-cell recognition [20], and (e) triggering of stress responses [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, new and potentially beneficial graft combinations are not explored due to compatibility barriers. Some incompatibility causes are: (a) genetic distance [7,15,16], (b) physiological and/or anatomical difficulties [14,17], (c) toxic compounds transference [18,19], (d) inadequate cell-to-cell recognition [20], and (e) triggering of stress responses [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Germination type is often indicative of evolutionary changes among clades [ 23 ], and one of the most relevant morphological traits that differentiates species [ 24 ]. According to Delgado-Salinas [ 6 ], P. coccineus subsp.…”
Section: Resultsmentioning
confidence: 99%
“…An intriguing example is the Solanaceae family where successful grafts have been commercially developed between either tomato or eggplant with potato producing effectively edible fruits from both the rootstock and the scion (TomTato ® and Egg and Chips ® of Thompson and Morgan). However, it was recently proven that plants from different families even distant ones can be grafted successfully (Notaguchi et al, 2020); phylogenetic proximity or similarity in the vascular anatomy of the grafting partners does not seem to result always in grafting realization (Wulf et al, 2020). It is shown that grafting is facilitated by the action of genes such as cellulases that help the reconstruction of cell walls; these genes can facilitate tissue adhesion and promote plant grafting (Kurotani et al, 2020;Notaguchi et al, 2020).…”
Section: Grafting Technics and Long-distance Signalingmentioning
confidence: 99%